Canine Genetics, Health and Medicine (IntechOpen, 2023)
The advances being made in veterinary medicine in the modern era are continuously pushing the boundaries of what is presently possible and available. From unraveling canine genetics and gene therapies to understanding the microbiome and the effects parasites have on canine health. Whilst many advances are being made with clinical diagnosis, surgeries, prosthetics, pharmaceuticals, and imaging techniques, preventative medicine is also at the forefront of technology. Our understanding of the medical issues, critical care, pharmaceutics, anatomy, pathology, genetics, and disease are all imperative in making advances in canine medicine. This book covers a diverse range of topics in canine health by highlighting recent and forthcoming canine medicine and health innovations and improvements.